Predictors of chronic heart failure development and progression in pre-dialysis patients with chronic kidney disease - Rodionova, V.V.; Boyko, O.O.; Turenko, O.A.; Denisenko, O.O. (KIDNEYS, 2021)
Background. Chronic kidney disease leads to early damage to the heart and blood vessels with the development of heart failure. The manifestation of one disease leads to the progression of another, since chronic heart failure is a condition in which the myocardium and kidneys are pathogenetically closely related to each other. The purpose of the work was to identify early predictors of chronic heart failure development and progression in patients with chronic kidney disease. Materials and methods. A retrospective analysis of case histories of 322 patients with chronic kidney disease stages 1–4 was carried out. Patients were divided into two groups: the main group included those with chronic kidney disease and chronic heart failure (n = 50), the comparison group — patients with chronic kidney disease, but without chronic heart failure (n = 50). We studied the data of clinical, laboratory and instrumental examination. The obtained results were processed statistically. Results. Patients with chronic kidney disease and signs of heart failure had an increased body mass index, leg swelling, and stage 2 hypertension degrees 1–2. The electrocardiograpy revealed a rhythm disturbance by the type of paroxysmal tachycardia and atrial fibrillation. A decrease in hemoglobin level, filtration function of the kidneys, as well as manifestations of dyslipidemia were detected. Conclusions. Diastolic hypertension, anemia and increased total cholesterol can be considered as early predictors of chronic heart failure in patients with chronic kidney disease. Consequently, the risk of heart failure development and progression increases with a decrease in glomerular filtration rate below 60 ml/min. Chronic heart failure develops earlier and progresses faster in patients with chronic kidney disease that developed as a result of chronic glomerulonephritis.